Draft Annual Plan 1988-89 Seventh Five Year Plan 1985-90 Scheme-Wise Details Government of Pondicherry Planning and Research Department - Planning Commission (Planning Commission, 1988)
There are no Scheduled Tribes in the Union Territory. The Territory constitutes a single revenue district consisting of 292 census villages, 129 revenue villages, 4 sub-taluks and 2 taluks. For the purpose of development administration the Territory is divided into 4 and 5/6 blocks consisting of 47 circles of village level workers. Pondicherry Panchayats Act of 1973 and Municipalities Act of 1973 came into force in 1974. There are 4 Municipalities namely, Pondicherry, Karaikal, Mahe and Yanam. There are 11 Commune Panchayats - 6 in Pondicherry region, namely, Ozukarai, Villianur, Mannadipet, Ariankuppam, Bahour, Nettapakkam and 5 in Karaikal region, namely, Thirunallar, Neravy, Nedungadu, Kottucherry and T.R. Pattinam.
Scheme-Wise Details
Government of Pondicherry